The usage of computer vision in the system of digital cutting of materials - Tumanov, V.V.; Doroshenko, А.Yu. (PROBLEMS IN PROGRAMMING, 2018)
An approach to the implementation of the computer vision system for recognizing and positioning objects on the cutting surface of machines for digital cutting of materials with the help of a photograph of their working surface with the marked cutting objects on it is proposed. Algorithms of the work of the system modules, which are responsible for the calibration of the camera, the recognition of registration marks by two fundamentally different methods, complemented each other, are developed. Also, an algorithm of identification of cutting objects on the basis of the application of elements of the graph theory is proposed.Problems in programming 2017; 4: 109-0118